Climate Risk Management in Agricultural Extension (CRMAE) Multistakeholder Curriculum Consultative Workshop in Zambia - Grossi, Amanda; Dinku, Tufa; Hansen, James (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A three-day multistakeholder consultative workshop was convened from March 1 to March 3, 2023, in Lusaka, Zambia by the Zambia Meteorological Department (ZMD), in close collaboration with the International Research Institute for Climate and Society (IRI) of the Columbia Climate School and the International Water Management Institute (IWMI). The workshop, which was organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project, brought together 15 participants representing agricultural extension and advisory service (EAS) providers across Zambia to co-design a curriculum to support climate risk management in agricultural extension.